2022
DOI: 10.1097/mao.0000000000003709
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Outcome Measures for Intratympanic Steroid Treatment for Idiopathic Sudden Sensorineural Hearing Loss

Abstract: Objective: To identify variability in reported hearing outcomes for intratympanic (IT) steroid treatment of idiopathic sudden sensorineural hearing loss (ISSNHL) by comparing outcomes using the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) guideline with other published criteria. Study Design: Retrospective chart review. Setting: Tertiary otology practice. Patients: Patients with ISSNHL treated with IT steroid between April 2003 and December 2020. Interventions: IT steroid injection and au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…14 The literature findings on the therapeutic effect of ITSIs are inconsistent; various definitions of hearing recovery have been proposed, and various demographics have been examined. 15 Koltsidopoulos et al 8 reported significant hearing recovery in 31 (67.39%) of 46 patients who underwent ITSI treatment. Siegel 11 used the final pure-tone audiometry (PTA) of the affected ear as a measure of recovery.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…14 The literature findings on the therapeutic effect of ITSIs are inconsistent; various definitions of hearing recovery have been proposed, and various demographics have been examined. 15 Koltsidopoulos et al 8 reported significant hearing recovery in 31 (67.39%) of 46 patients who underwent ITSI treatment. Siegel 11 used the final pure-tone audiometry (PTA) of the affected ear as a measure of recovery.…”
Section: Discussionmentioning
confidence: 98%
“…The results for delayed treatment group were comparable with previous studies: Haynes et al 19 reported 15.79% of cases improved hearing after the delayed salvage ITSIs (time to injection >1 month), using the criteria of 20-dB gain in PTA. As the primary but delayed ITSIs treatment and using AAO-HNS reporting criteria, Osafo et al 15 published the recovery rate after ITSIs was slightly more than 20%. Our results, with a larger sample size, offer more robust evidence for this matter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ITS provides a higher concentration of steroids in perilymph compared with systemic steroid therapy (Xenellis et al 2006). American Academy of Otolaryngology-Head and Neck Surgery has clinical practice guidelines that recommend the use of ITS as salvage therapy in cases of incomplete recovery 2 to 6 weeks after symptom onset (Xenellis et al 2006; Osafo et al 2022). HBO therapy is thought to increase oxygen tension in the blood and inner ear.…”
Section: Introductionmentioning
confidence: 99%